2014
DOI: 10.1007/978-3-319-04546-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Automated Structural Damage Detection Using One-Class Machine Learning

Abstract: Measuring and analysing the vibration of structures using sensors can help identify and detect damage, potentially prolonging the life of structures and preventing disasters. Wireless sensor systems promise to make this technology more affordable and more widely applicable. Data driven structural health monitoring methodologies take raw signals obtained from sensor networks, and process them to obtain damage sensitive features. New measurements are then compared with baselines to detect damage. Because damage-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…This current study has only identified the resonant frequency from the antenna tower. If the system were to be used for structural health monitoring possible methods for monitoring changes in the displacement signal include statistical pattern recognition techniques (Sohn et al 2001), one-class machine learning methods (Long and Buyukozturk 2014), analysis of nonlinear features (Mohammadi Ghazi and Büyüköztürk 2016), or other damage detection algorithms. Without the need for physical access to instrument a structure, cameras can more easily collect data from structures that might otherwise be difficult or time consuming to instrument.…”
Section: Discussionmentioning
confidence: 99%
“…This current study has only identified the resonant frequency from the antenna tower. If the system were to be used for structural health monitoring possible methods for monitoring changes in the displacement signal include statistical pattern recognition techniques (Sohn et al 2001), one-class machine learning methods (Long and Buyukozturk 2014), analysis of nonlinear features (Mohammadi Ghazi and Büyüköztürk 2016), or other damage detection algorithms. Without the need for physical access to instrument a structure, cameras can more easily collect data from structures that might otherwise be difficult or time consuming to instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Several kernel functions have been used in SVM such as Gaussian and polynomial kernels. However, Gaussian kernel defined in Equation has gained much popularity in the area of machine learning, and it showed a high potential to be an appropriate setting for OCSVM . This kernel function has a user defined parameter denoted by σ , which determines the width of the Gaussian kernel and can hysterically affect the performance of the OCSVM.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…However, Gaussian kernel defined in Equation (11) has gained much popularity in the area of machine learning, and it showed a high potential to be an appropriate setting for OCSVM. [19][20][21] This kernel function has a user defined parameter denoted by σ, which determines the width of the Gaussian kernel and can hysterically affect the performance of the OCSVM. This parameter may yield to overfit the model if it receives small values and underfit in case of large values.…”
Section: Self-tuning: Gaussian Kernel Parametersmentioning
confidence: 99%
“…Large values of σ underfit the data, resulting in an inability to detect non‐trivial patterns. Long and Buyukozturk investigated three potential methods for automatic selection of this parameter, and found the method developed by Khazai et al to give good results. This method is also used for this paper.…”
Section: Statistical Pattern Recognitionmentioning
confidence: 99%